2012
DOI: 10.1128/aac.00164-12
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of U.S. Marketplace Vancomycin for Injection Products Using High-Resolution Liquid Chromatography-Mass Spectrometry and Potency Assays

Abstract: In response to a published concern about the potency and quality of generic vancomycin products, the United States Food and Drug Administration investigated a small sampling of the vancomycin products available in North America with regard to purity, content, and potency. To facilitate identification of impurities, a new liquid chromatography method was developed using high-resolution mass spectrometry in addition to diode array detection to characterize impurities in several commercial products. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 20 publications
(23 reference statements)
3
22
1
Order By: Relevance
“…There has been an intense debate worldwide, involving the scientific community, drug regulatory agencies, and the public, about the therapeutic equivalence of generic antibiotics, especially vancomycin (14,15). A source of the debate is data published by our group in the past 10 years, demonstrating that pharmaceutical equivalence is a necessary but not sufficient condition to ensure therapeutic equivalence.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an intense debate worldwide, involving the scientific community, drug regulatory agencies, and the public, about the therapeutic equivalence of generic antibiotics, especially vancomycin (14,15). A source of the debate is data published by our group in the past 10 years, demonstrating that pharmaceutical equivalence is a necessary but not sufficient condition to ensure therapeutic equivalence.…”
Section: Discussionmentioning
confidence: 99%
“…Analytical chemistry data for six vancomycin generics obtained by FDA scientists demonstrated that factor B and total impurities made up 90 to 95% and 5 to 10%, respectively, which was in full compliance with the U.S. Pharmacopeia (11)(12)(13). Similarly, no significant differences were detected among six French vancomycin generics based on the rabbit endocarditis model used by scientists from the Pontchaillou University Hospital at Rennes (14).…”
mentioning
confidence: 99%
“…These studies were done several years after the innovator had abandoned antimicrobial business, selling its vancomycin production secrets to all interested parties, while our research took place before and after that decision (7,8). The discontinuation of the innovator made vancomycin a less-than-ideal choice to study the mechanisms behind therapeutic nonequivalence, but the FDA reports showed that U.S. generics differed slightly in the amounts and variety of impurities and degradation products (11,12). Although such differences do not violate the pharmacopeia, the fact is that vancomycin generics are not chemically identical.…”
mentioning
confidence: 99%
“…In the absence of compendial methods, manufacturers of these products must develop and validate their own (noncompendial) analytical methods and product specifications [21]. Manufacturers are also responsible for verifying that analytical methods used for product stability testing are suitably capable of detecting, and as necessary quantifying, degradation products.…”
Section: Analytical Methods Used In Production Operationsmentioning
confidence: 99%
“…The term 'analytical' in PAT is viewed broadly to include chemical, physical, microbiological, mathematical, and risk analysis conducted in an integrated manner" [21]. The concept marries analytical technology, process development tools (such as statistically designed experiments), mathematical modeling, and risk assessment tools (such as failure modes effects analysis) to define the most effective testing and control scheme to best assure the consistent quality of the manufactured product.…”
Section: Analytical Methods Used In Production Operationsmentioning
confidence: 99%